2002
DOI: 10.1002/1521-3765(20020703)8:13<2868::aid-chem2868>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Carbon Nanofibres for the Immobilization of Metal Complexes: A Case Study with Rhodium and Anthranilic Acid

Abstract: The immobilisation of the rhodium/anthranilic acid complex onto fishbone carbon nanofibres (CNFs) was executed by means of the following steps: 1) surface oxidation of the fibres, 2) conversion of the oxygen-containing surface groups into acid chloride groups, 3) attachment of anthranilic acid and 4) complexation of rhodium by the attached anthranilic acid. The immobilisation process was followed and the resulting surface species were characterised by IR, X-ray absorption fine structure (XAFS) and X-ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…49 The immobilization of a rhodium/anthranilic acid complex onto CNFs-h was executed by means of the following steps: (1) CNF surface oxidation, (2) conversion of the oxygen-containing surface groups into acid chloride groups, (3) attachment of anthranilic acid and (4) complexation of rhodium by the attached anthranilic acid (Figure 7.2(c)). 50 The as-synthesized Rh III complex itself is not active in the liquid-phase hydrogenation of cyclohexene. However, reduction with sodium borohydride yields small particles (d = 1.5-2 nm) of rhodium metal that are highly active.…”
Section: Alkene and Alkyne Hydrogenationmentioning
confidence: 99%
“…49 The immobilization of a rhodium/anthranilic acid complex onto CNFs-h was executed by means of the following steps: (1) CNF surface oxidation, (2) conversion of the oxygen-containing surface groups into acid chloride groups, (3) attachment of anthranilic acid and (4) complexation of rhodium by the attached anthranilic acid (Figure 7.2(c)). 50 The as-synthesized Rh III complex itself is not active in the liquid-phase hydrogenation of cyclohexene. However, reduction with sodium borohydride yields small particles (d = 1.5-2 nm) of rhodium metal that are highly active.…”
Section: Alkene and Alkyne Hydrogenationmentioning
confidence: 99%
“…After reaction about 30 min at 0 8C, the mixture was stirred at room temperature for 2 days. After filtration and removal of all the solvents under reduced pressure, the obtained residue was recrystallized with a mixture of dichloromethane/pentane (v/vZ1/2) to give 4.41 g (7) in 83% yield. …”
Section: Synthesis and Characterization Ofmentioning
confidence: 99%
“…Although the detail mechanisms have not yet been disclosed, it has been found that carbon nanotubes are promising catalyst supports with improved catalytic activities after immobilization of homogeneous catalysts [6][7][8][9]. It is known that the existing ZieglerNatta catalytic systems for olefin polymerization are not able to tolerate polar monomers such as vinyl chloride, acrylate, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In many of these applications, CNTs have to be surface functionalized [8]. Among various surface functionalization techniques, oxidation is probably the most widely studied.…”
Section: Introductionmentioning
confidence: 99%